Pigment epithelium-derived factor: Clinical significance in estrogen-dependent tissues and its potential in cancer therapy (2015)
Pigment epithelium-derived factor (PEDF) is a glycoprotein that belongs to the family of noninhibitory serpins. The broad spectrum of PEDF biological activity is evident when considering its effects in promoting cell survival and proliferation, as well as its antiangiogenic, antitumor, and antimetastatic properties. Although the structural domains of the PEDF gene that mediate such diverse effects and their mechanisms of action have not been completely elucidated, there is a large body of evidence describing their diverse range of activities; this evidence combined with the regulation of PEDF expression by sex steroids and their receptors have led to the idea that PEDF is not only a diagnostic and prognostic marker for certain diseases such as cancer, but is also a potential therapeutic target. In this manner, this paper aims to generally review the regulation of PEDF expression and PEDF interactions, as well as the findings that relate PEDF to the role of estrogens and estrogen receptors. In addition, this manuscript will review major advances toward potential therapeutic applications of PEDF. © 2015, Mashhad University of Medical Sciences. All rights reserved.